The global burden of perinatal common mental health disorders and substance use among migrant women: a systematic review and meta-analysis. (March 2023) - Stevenson, Kerrie; Fellmeth, Gracia; Edwards, Samuel; Calvert, Clara; Bennett, Phillip; Campbell, Oona M R; Fuhr, Daniela C
Summary: Background: There are one billion migrants globally, of whom 82 million are forced migrants. Pregnant migrants face pre-migration stressors such as conflict, transit stressors including poverty, and post-migration stressors including navigating the immigration system; these stressors can make them vulnerable to mental illness. We aimed to assess the global prevalence of and risk factors for perinatal mental health disorders or substance use among women who are migrants. Methods: In this systematic review and meta-analysis, we searched OVID MEDLINE, Embase, PsycINFO, CENTRAL, Global Health, Scopus, and Web of Science for studies published from database inception until July 8, 2022. Cohort, cross-sectional, and interventional studies with prevalence data for any mental illness in pregnancy or the postnatal period (ie, up to a year after delivery) or substance use in pregnancy were included. The primary outcome was the prevalence of perinatal common mental health disorders among women who are migrants, globally. Data for study quality and risk factors were also extracted. A random-effects meta-analysis was used to calculate pooled prevalence estimates, when appropriate. Sensitivity analyses were conducted according to study quality, sample representativeness, and method of outcome assessment. Risk factor data were synthesised narratively. This study is registered with PROSPERO, CRD42021226291. Findings: 18 650 studies were retrieved, of which 135 studies comprising data from 621 995 participants met the inclusion criteria. 123 (91%) of 135 studies were conducted in high-income host countries. Five (4%) of 135 studies were interventional, 40 (30%) were cohort, and 90 (66%) were cross-sectional. The most common regions of origin of participants were South America, the Middle East, and north Africa. Only 26 studies presented disaggregated data for forced migrants or economic migrants. The pooled prevalence of perinatal depressive disorders was 24·2% (range 0·5–95·5%; I 2 98·8%; τ 2 0·01) among all women who are migrants, 32·5% (1·5–81·6; 98·7%; 0·01) among forced migrants, and 13·7% (4·7–35·1; 91·5%; 0·01) among economic migrants (p<0·001). The pooled prevalence of perinatal anxiety disorders was 19·6% (range 1·2–53·1; I 2 96·8%; τ 2 0·01) among all migrants. The pooled prevalence of perinatal post-traumatic stress disorder (PTSD) among all migrant women was 8·9% (range 3·2–33·3; I 2 97·4%; τ 2 0·18). The pooled prevalence of perinatal PTSD among forced migrants was 17·1% (range 6·5–44·3; I 2 96·6%; τ 2 0·32). Key risk factors for perinatal depression were being a recently arrived immigrant (ie, approximately within the past year), having poor social support, and having a poor relationship with one's partner. Interpretation: One in four women who are migrants and who are pregnant or post partum experience perinatal depression, one in five perinatal anxiety, and one in 11 perinatal PTSD. The burden of perinatal mental illness appears higher among women who are forced migrants compared with women who are economic migrants. To our knowledge, we have provided the first pooled estimate of perinatal depression and PTSD among women who are forced migrants. Interpreting the prevalence estimate should be observed with caution due to the very wide range found within the included studies. Additionally, 66% of studies were cross-sectional representing low quality evidence. These findings highlight the need for community-based routine perinatal mental health screening for migrant communities, and access to interventions that are culturally sensitive, particularly for forced migrants who might experience a higher burden of disease than economic migrants. Funding: UK National Institute for Health Research (NIHR); March of Dimes European Preterm Birth Research Centre, Imperial College; Imperial College NIHR Biomedical Research Centre; and Nuffield Department of Population Health, University of Oxford.